2017
DOI: 10.1111/1440-1681.12810
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CYP2C8 and CYP2C9 amino acid substitution alleles in South Indian diabetes patients: A genotypic and computational protein phenotype study

Abstract: The CYP2C8 and CYP2C9 are two major isoforms of the cytochrome P450 enzyme family, which is involved in drug response, detoxification, and disease development. This study describes the differential distribution of amino acid substitution variants of CYP2C8 (*2-I269F & *3-R139K) and CYP2C9 (*2-C144R & *3-L359A) genes in 234 type 2 diabetes mellitus (T2DM) patients and 218 healthy controls from Andhra Pradesh, South India. Single locus genotype analysis has revealed that homozygous recessive genotypes of 2C8*2-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In fact, there were no other genetic studies of type 2 diabetes in the population of Hyderabad when the corresponding author of this manuscript initiated a project in the year 2009 at the Indian Statistical Institute (ISI), Hyderabad, and 15 SNPs belonging to nine genes that were known to be involved in blood-glucose homeostasis—TCF7L2 [ 19 ], insulin secretion and action-IGF2BP2 and SLC30A8 [ 20 ], insulin signaling pathway and adipocyte differentiation—IRS1, CAPN10 and PPARG [ 21 ] and pancreatic beta cell development-CDKAL1, CDKN2A/B and HHEX [ 22 ] were genotyped. Further studies of T2DM in Hyderabad were too scanty and focused only on a couple of genes/SNPs [ 23 25 ]. Overall, the results among the Indian populations were found to be largely inconsistent with exception to a few SNPs—rs7903146 and rs12255372 of TCF7L2, rs2970847 of PGC-1α, rs9939609 of FTO, rs1801282 of PPARG, rs4402960 of IGF2BP2 and rs5219 of KCNJ11 [ 9 11 , 19 , 26 32 ] that showed a relatively greater degree of consistency in their association with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there were no other genetic studies of type 2 diabetes in the population of Hyderabad when the corresponding author of this manuscript initiated a project in the year 2009 at the Indian Statistical Institute (ISI), Hyderabad, and 15 SNPs belonging to nine genes that were known to be involved in blood-glucose homeostasis—TCF7L2 [ 19 ], insulin secretion and action-IGF2BP2 and SLC30A8 [ 20 ], insulin signaling pathway and adipocyte differentiation—IRS1, CAPN10 and PPARG [ 21 ] and pancreatic beta cell development-CDKAL1, CDKN2A/B and HHEX [ 22 ] were genotyped. Further studies of T2DM in Hyderabad were too scanty and focused only on a couple of genes/SNPs [ 23 25 ]. Overall, the results among the Indian populations were found to be largely inconsistent with exception to a few SNPs—rs7903146 and rs12255372 of TCF7L2, rs2970847 of PGC-1α, rs9939609 of FTO, rs1801282 of PPARG, rs4402960 of IGF2BP2 and rs5219 of KCNJ11 [ 9 11 , 19 , 26 32 ] that showed a relatively greater degree of consistency in their association with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…The reported findings demonstrated that ID is involved diversified phenotypic characteristics rather than described with single feature [30]. A genotyping study for celiac disease on Saudi Arabian population was evident potential susceptible locus using bio-statistical analysis [31] and another study on South Indian diabetic patients was signified the result by correlating genotypic and computational approach [32]. Our approach to the current study was based on the necessity to understand the genotype-phenotype consequences and computational protein phenotype predictions in intellectually disabled children of Western Indian population.…”
Section: Discussionmentioning
confidence: 86%
“…Intellectual Disability (ID) is a prominent characteristic in most of the neurodevelopmental disorders affecting health, teaching and community services in growing nations. A meta-analysis of international studies reported the prevalence of intellectual disability between 1% and 3% of the worldwide population [1]; the world health organization characterized this clinical condition by Intelligence Quotient (IQ) score of less than 70; mild (55-70), moderate (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and profound (<20) [2]. The environmental factors such as maternal alcohol abuse during pregnancy, infections, birth complications and extreme malnutrition are major causes of ID.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that combined therapy with insulin and aspartame in diabetic rats induced CYP2E1 in the brain, which could have toxicological effects [31]. Another study in India indicated the variable distribution of CYP2C8 and CYP2C9 allelic polymorphisms in people with diabetes [32]. Study showed that ER stress is involved in molecular process of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%